Production and Maintenance Optimization Problems : Logistic Constraints and Leasing Warranty Services. - Rezg, Nidhal (Systems and Industrial Engineering - Robotics Series, 2016)
Focuses on industrial constraints such as subcontracting, warranty, and quality in manufacturing and logistic fields and gives new integrated maintenance strategies.